2020
DOI: 10.1167/tvst.9.2.50
|View full text |Cite
|
Sign up to set email alerts
|

Piloting a Deep Learning Model for Predicting Nuclear BAP1 Immunohistochemical Expression of Uveal Melanoma from Hematoxylin-and-Eosin Sections

Abstract: Piloting a deep learning model for predicting nuclear BAP1 immunohistochemical expression of uveal melanoma from hematoxylin-and-eosin sections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…While our results need further verification in different experimental settings, the CIBERSORTx algorithm we employed has been extensively validated with techniques such as flow cytometry, mass cytometry, immunohistochemistry, and single-cell RNA-seq by multiple different groups, providing robust data confirming its accuracy [40,[63][64][65]. Nevertheless, others have already created mRNA/miRNA/DNA-based scores with strong prognostic values in UM tumors [33,[66][67][68][69][70][71][72]. Rather than compete with them, our foremost motive for creating the cell type-based prognostic score was to select the cell types playing a prime role in the biology of UM progression Previous research has identified extensive lymphocyte infiltration as a negative prognostic factor in UM; however, the prognostic role of individual subsets was not assessed Another dominant subset of tumor-infiltrating immune cells is macrophages.…”
Section: Journal Of Immunology Researchmentioning
confidence: 75%
“…While our results need further verification in different experimental settings, the CIBERSORTx algorithm we employed has been extensively validated with techniques such as flow cytometry, mass cytometry, immunohistochemistry, and single-cell RNA-seq by multiple different groups, providing robust data confirming its accuracy [40,[63][64][65]. Nevertheless, others have already created mRNA/miRNA/DNA-based scores with strong prognostic values in UM tumors [33,[66][67][68][69][70][71][72]. Rather than compete with them, our foremost motive for creating the cell type-based prognostic score was to select the cell types playing a prime role in the biology of UM progression Previous research has identified extensive lymphocyte infiltration as a negative prognostic factor in UM; however, the prognostic role of individual subsets was not assessed Another dominant subset of tumor-infiltrating immune cells is macrophages.…”
Section: Journal Of Immunology Researchmentioning
confidence: 75%
“…With the rapidly growing number of digital image analysis and artificial intelligence solutions for assisting pathologists with diagnosis, treatment prediction and prognostication, further developments in this field should be expected. [37][38][39][40][41] Further, severe anaplasia correlated strongly with gain of chromosome 6p. The central part of the short arm of chromosome 6p has been reported to harbor oncogenes that are linked to tumor progression and gains at 6p have been associated with metastatic disease and poor prognosis in other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a DenseNet neural network architecture outperformed three other state-of-the-art neural network architectures, as well as a support vector machine. A later study by Zhang et al reportedly outperformed these results using a larger data set [51]. Here, a ResNet18 model was used to extract feature vectors from tiles before assembling a set of feature vectors corresponding to a single slide into a feature map according to their spatial locations.…”
Section: Predicting Gene Expression and Hormone Receptor Statusmentioning
confidence: 98%